Efektivitas LAPOR! Dalam Upaya Peningkatan Kualitas Layanan Publik di Kabupaten Bolaang Mongondow Selatan - Usman, Nur’adin Feriyanto; Arifin; Puyo, Marten (Melati Institute, 2024)
This research examines the effectiveness of the LAPOR! (People's Online Aspiration and Complaint Service) platform as a tool to improve the quality of public services in South Bolaang Mongondow Regency. LAPOR! is designed to facilitate the public in submitting aspirations and complaints through digital channels. Although it has been implemented since 2018, the number of complaints submitted in the district is still very low compared to the national average, indicating challenges in its adoption and utilization. The research used a case study approach to explore the level of community participation, the admin's ability to manage reports, and the platform's role in supporting government transparency and responsiveness. The results show that low digital literacy and limited infrastructure are major barriers. However, when optimized, LAPOR! has the potential to be an effective tool to improve government-community relations, accelerate complaint handling, and promote public service accountability. This research recommends strengthening digital literacy, training admins, and improving access to technology to maximize the function of LAPOR! in South Bolaang Mongondow District.